2003
DOI: 10.1104/pp.103.026104
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Integration of T-DNA into the Tobacco Genome at Double-Stranded Breaks: New Insights on the Mechanism of T-DNA Integration

Abstract: Agrobacterium tumefaciens T-DNA normally integrates into random sites in the plant genome. We have investigated targeting of T-DNA by nonhomologous end joining process to a specific double-stranded break created in the plant genome by I-CeuI endonuclease. Sequencing of genomic DNA/T-DNA junctions in targeted events revealed that genomic DNA at the cleavage sites was usually intact or nearly so, whereas donor T-DNA ends were often resected, sometimes extensively, as is found in random T-DNA inserts. Short fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
106
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 33 publications
0
106
0
2
Order By: Relevance
“…More importantly, T-DNA molecules can be digested by rarecutting restriction enzymes prior to their final integration into the plant genome (Chilton and Que, 2003;Tzfira et al, 2003). These observations indicate that it is the dsT-DNA intermediates that function as substrates for the NHEJ integration machinery (Chilton and Que, 2003;Tzfira et al, 2003). Furthermore, sequencing analysis indicates that the digested dsT-DNA molecules may be integrated into the rare-cutter-induced genomic DSBs by a simple NHEJ ligation-like mechanism (Chilton and Que, 2003;Tzfira et al, 2003).…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…More importantly, T-DNA molecules can be digested by rarecutting restriction enzymes prior to their final integration into the plant genome (Chilton and Que, 2003;Tzfira et al, 2003). These observations indicate that it is the dsT-DNA intermediates that function as substrates for the NHEJ integration machinery (Chilton and Que, 2003;Tzfira et al, 2003). Furthermore, sequencing analysis indicates that the digested dsT-DNA molecules may be integrated into the rare-cutter-induced genomic DSBs by a simple NHEJ ligation-like mechanism (Chilton and Que, 2003;Tzfira et al, 2003).…”
mentioning
confidence: 87%
“…These observations indicate that it is the dsT-DNA intermediates that function as substrates for the NHEJ integration machinery (Chilton and Que, 2003;Tzfira et al, 2003). Furthermore, sequencing analysis indicates that the digested dsT-DNA molecules may be integrated into the rare-cutter-induced genomic DSBs by a simple NHEJ ligation-like mechanism (Chilton and Que, 2003;Tzfira et al, 2003). These observations led us to suggest that NHEJ-mediated gene replacement might be achieved by coupling the release of a target DNA portion (by the expression of ZFN enzymes) with the delivery of donor T-DNA molecules.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…However, evidence for such a reaction has not been obtained. It has been shown that T-DNA preferentially integrates at double-strand breaks in plant cells (Salomon & Puchta, 1998;Chilton & Que, 2003) and in yeast (van Attikum & Hooykaas, 2003). A role of VirD2 in integration at double-strand breaks has not yet been shown.…”
Section: Discussionmentioning
confidence: 99%